Green Leadership and Corporate Social Responsibility: Study of Community Responses to CSR Activities PT. Pertamina Fuel Terminal Boyolali - Widiartanto Widiartanto; Fendy Eko Wahyudi; Bayu Pradika; Bima Adistya; Amni Z. Rahman; Satwika Paramasatya (Universitas Diponegoro, 2023)
This research is motivated by the phenomenon that in order to strengthen corporate sustainability, the concept of Corporate Social Responsibility (CSR) Sustainability prioritizes corporate responsibility to society with the concept of sustainable development. Means that companies need to pay attention to environmental, community, and stakeholders that emphasize the implementation of sustainable programs. This study aims to determine the implementation of green leadership in the company and determine the satisfaction and independence of the beneficiaries of PT. Pertamina Fuel Terminal Boyolali. The research locations are in the villages of Tawangsari, Mojolegi, Teras, and Blumbang which are assisted villages. This type of research is descriptive quantitative with a sample of 146 people spread across 12 CSR programs. The results of the study show that the implementation of green leadership in companies has been going well, both within the company and community through CSR activities. Overall, it can be seen that the Community Satisfaction Index Score from 2017 to 2020 is a very good category, between the intervals of 81.26 to 100. Meanwhile, in terms of independence, 12 CSR programs in 2018 have produced a good level of independence. Proof that 70% of CSR programs are at high independence.